STUDI PENERAPAN METODE LOAD ORIENTED MANUFACTURING CONTROL (LOMC) DALAM PEMENUHAN WAKTU PENERIMAAN PESANAN DI PT. XXX - Dewi Sari Kencana; Mangara M; Aulia Ishak (Jurnal Teknik Industri USU, 2013)
The accuracy in fulfilling orders which has been promised by the company and the quality of the product which conformed with expectation, as well as a fee charged was elements of satisfaction that must be fulfilled by the company. PT. XXX  is a manufacturing company  which active in the fields of making concrete products, namely PC Piles and PC Pole. Based on data from the company, the company is only able to meet the SPK (work orders) as much as 15 projects (71,43%) and within schedule was 21 projects, the rest as much as 6 projects (28,57%) was late in completion. This research aimed is to determine the received date by using Load Oriented Manufacturing Control methods which are calculations of manufacturing lead time, considered time of delivery  an order to the consumer, the capacity available at every station work, time process on work stations and the flow of production. By using the Load Oriented Manufacturing Control method and considering an available capacity, delivery time and order priority, then received date of order type of PC A 400(1) is 3 days, a type of PC A 400(2) is 5 days a type of PC A 400(3) is 9 days, a type of PC A 350(1) is 6 days, a type of PC A 350(2) is 8 days, and type of pc a 300  is 7 days are obtained. It showed that the calculation of order received determination by using the Load Oriented Manufacturing Control (LOMC) methods compare to actual method is more accurate.